IMPLEMENTATION OF HEALTH SERVICES FOR ELDERLY PRISONERS IN CLASS IIA KUNINGAN PRISON - Hamzah, Abdulah Nur; Santoso, Imam (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study examines the implementation of healthcare services for elderly inmates at the Kuningan Class IIA Correctional Facility, highlighting both the achievements and challenges encountered in providing adequate care. Despite the positive and transparent relationship between prison staff and elderly inmates, the quality of healthcare has not reached an optimal level due to limited human resources and inadequate medical facilities. The research employs a qualitative methodology, utilizing interviews and observations to gather insights from healthcare staff and elderly inmates about their experiences and perceptions of the healthcare services offered. The findings reveal that while the staff shows dedication and empathy towards the inmates, significant improvements are necessary to enhance the quality of healthcare service. This study aims to provide a comprehensive understanding of the current state of healthcare for elderly inmates and suggest actionable strategies for enhancing service delivery in correctional settings. Keywords: Health Service; Inmates; Elderly